Exploring the Spirit of Chinese Entrepreneurs in the New Era through the Theory of "Cheng" in The Doctrine of the Mean - Qu, Mingyang (Education Insights, 2026)
Against the backdrop of China's economy transitioning towards high-quality development and the continuous strengthening of social supervision and management systems, the entrepreneurial spirit that once prioritized rapid economic growth, with survival and profit as its core, is no longer aligned with the demands of the times. The spirit of Chinese entrepreneurs must now shift towards focusing on long-term value creation, achieving technological innovation, upholding integrity and trustworthiness, and actively assuming social responsibilities. This paper will construct an analytical framework based on the concept of "Cheng" (sincerity/authenticity) from The Doctrine of the Mean, embed it within existing theories on entrepreneurial spirit, and use this approach to explore and elucidate the connotations of the spirit of Chinese entrepreneurs in the new era.